Northern Hemisphere Climatology and Interannual Variability of Storm Tracks in NCEP’s CFS Model - Timothy Paul Eichler; Francisco Alvarez; Jon Gottschalck (Advances in Meteorology)
Evaluating the climatology and interannual variability of storm tracks in climate models represents an excellent way to evaluate their ability to simulate synoptic-scale phenomena. We generate storm tracks from the National Center for Environmental Prediction (NCEP) Climate Forecast System (CFS) model for the northern hemisphere (NH) and compare them to storm tracks generated from NCEP’s reanalysis I data, the European Centre for Medium Range Prediction (ECMWF) ERA40 data, and CFS reanalysis data. To assess interannual variability, we analyze the impacts of El Niño, the North Atlantic Oscillation (NAO), and the Indian Ocean Dipole (IOD). We show that the CFS model is capable of simulating realistic storm tracks for frequency and intensity in the NH. The CFS storm tracks exhibit a reasonable response to El Niño and the NAO. However, it did not capture interannual variability for the IOD. Since one path by which storm tracks respond to external forcing is via Rossby waves due to anomalous heating, the CFS model may not be able to capture this effect especially since anomalous heating for the IOD is more local than El Niño. Our assessment is that the CFS model’s storm track response is sensitive to the strength of external forcing.